1992
DOI: 10.4319/lo.1992.37.6.1129
|View full text |Cite
|
Sign up to set email alerts
|

The phosphorus cycle in coastal marine sediments

Abstract: Approximately half of the sedimentation flux of particulate phosphorus in the Laurentian Trough in the Gulf of St. Lawrence is mobilized within the sediment and returned to the water column. In the oxidizing surface sediment, a major portion of the sedimentation flux of organic phosphorus is mineralized, and the released phosphate is partitioned between the pore water and surface adsorption sites. Surface-adsorbed phosphate is released to the pore water as needed to replace dissolved phosphate that escapes to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
173
0
7

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 462 publications
(196 citation statements)
references
References 33 publications
16
173
0
7
Order By: Relevance
“…The phosphate release from iron and manganese oxides in anoxic conditions (Sundby et al, 1992) is also confirmed by higher phosphate pore water concentrations in cohesive-muddy stations (A and B) compared to sandy permeable stations (D and F; Figure 7). Pore water profiles also showed that phosphate concentrations remained constant down to 10 cm sediment depth in sandy stations D and F (Figure 7) indicating the lack of iron and manganese reductions within these depths.…”
Section: Phosphate Sediment-water Fluxesmentioning
confidence: 64%
See 4 more Smart Citations
“…The phosphate release from iron and manganese oxides in anoxic conditions (Sundby et al, 1992) is also confirmed by higher phosphate pore water concentrations in cohesive-muddy stations (A and B) compared to sandy permeable stations (D and F; Figure 7). Pore water profiles also showed that phosphate concentrations remained constant down to 10 cm sediment depth in sandy stations D and F (Figure 7) indicating the lack of iron and manganese reductions within these depths.…”
Section: Phosphate Sediment-water Fluxesmentioning
confidence: 64%
“…Pore water profiles also showed that phosphate concentrations remained constant down to 10 cm sediment depth in sandy stations D and F (Figure 7) indicating the lack of iron and manganese reductions within these depths. Conversely, muddy stations A and B showed an increase of phosphate with sediment depth until 5-6 cm depth and remained constant below these horizons indicating that iron and manganese reduction dominated the organic matter mineralisation pathways in the upper sediment layers in these stations (Fenchel and Jørgensen, 1977;Froelich et al, 1979;Sundby et al, 1992).…”
Section: Phosphate Sediment-water Fluxesmentioning
confidence: 99%
See 3 more Smart Citations